Selection Of DTH Operator Using Improved Accuracy Function On Trapezoidal Intuitionistic Fuzzy Numbers - Edwin Antony Raj. M , Geetha Sivaraman, Vishnukumar. P (International Journal of Advanced Science and Technology, 2020)
MCDM can be solved by distinct methods such as genetic algorithm, neuro fuzzy algorithm, granular computing. Since sometimes the information gathered from the experts are in the various form of Intuitionistic Fuzzy Numbers like Trapezoidal Intuitionistic Fuzzy Numbers. In this paper, improved accuracy function on Interval valued intuitionistic fuzzy Number is extended into Trapezoidal Intuitionistic Fuzzy Number. To show the potency of the proposed technique compared with existing methods, counter examples are given. Some of the properties of the proposed technique are also discussed. In a real life situation, we may come across many practical problems. Here we have taken one of the problem i.e selecting one DTH operator among set of six operators. This problem is solved by the proposed method using TOPSIS technique.